URGENSI PENGEMBANGAN KEMAMPUAN BERPIKIR MATEMATIS SISWA SEKOLAH DASAR DALAM KONTEKS PENDIDIKAN ABAD KE-21 - Syahrial, Syahrial; Saragih, Doni Irawan; Siregar, Husnah; Syahara, Nabila; Putri, Sasri Agustina (Jurnal Merah Putih Sekolah Dasar, 2025)
The twenty-first century is characterized by rapid developments in science, technology, and information, which require students to possess higher-order thinking skills. One essential skill that needs to be developed from the elementary school level is mathematical thinking ability. This ability is not limited to mastering mathematical concepts and procedures, but also includes logical, critical, and systematic reasoning, as well as problem-solving skills in real-life contexts. This article aims to examine the development of elementary school students’ mathematical thinking skills in response to the challenges of twenty-first-century education. The study employed a qualitative approach using a literature review method by analyzing relevant academic sources, including journals, books, and research articles. The findings indicate that the development of mathematical thinking skills can be effectively enhanced through twenty-first-century learning approaches that are student-centered, problem-based, project-based, contextual, and supported by the integration of technology. In addition, the role of teachers and a supportive school environment is crucial in fostering students’ reflective and creative thinking habits. Strengthening mathematical thinking skills from an early age is expected to equip students to become adaptive, solution-oriented, and well-prepared to face future life challenges.